Gonadal Rejuvenation of Mice by Growth Differentiation Factor 11. Issue 5 (13th November 2021) - Zhou, Yang; Ni, Shousheng; Li, Congjun; Song, Lili; Zhang, Shicui
Abstract: Growth differentiation factor 11 (GDF11), also known as bone morphogenetic protein 11, has been shown to have rejuvenation and antiaging properties, but little information is available regarding the role of GDF11 in reproductive system to date. In this study, we first confirmed the bioavailability of recombinant GDF11 (rGDF11) by oral delivery in mice. We also showed that dietary intake of rGDF11 had little influence on body and gonadal (ovary/testis) weights of recipient mice, indicating their general condition and physiology were not affected. Based on these findings, we started to test the function of rGDF11 in ovary and testis of mice and to explore the underlying mechanisms. It was found that to some extent, rGDF11 could attenuate the senescence of ovarian and testicular cells, and contribute to the recovery of ovarian and testicular endocrine functions. Moreover, rGDF11 could rescue the diminished ovarian reserve in female mice and enhance the activities of marker enzymes of testicular function (sorbitol dehydrogenase and glucose-6-phosphate dehydrogenase) in male mice, suggesting a potential improvement of fertility. Notably, rGDF11 markedly promoted the activities of antioxidant enzymes in the ovary and testis, and remarkably reduced the levels of lipid peroxidation, protein oxidation, and reactive oxygen species (ROS) in the ovary and testis. Collectively, these results suggest that GDF11 can protect ovarian and testicular functions of aged mice via slowing down the generation of ROS through enhancing activities of antioxidant enzymes.